2000
DOI: 10.1073/pnas.97.4.1867
|View full text |Cite
|
Sign up to set email alerts
|

Gamma rhythms and beta rhythms have different synchronization properties

Abstract: Experimental and modeling efforts suggest that rhythms in the CA1 region of the hippocampus that are in the beta range (12-29 Hz) have a different dynamical structure than that of gamma (30 -70 Hz). We use a simplified model to show that the different rhythms employ different dynamical mechanisms to synchronize, based on different ionic currents. The beta frequency is able to synchronize over long conduction delays (corresponding to signals traveling a significant distance in the brain) that apparently cannot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

54
683
3
7

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 955 publications
(771 citation statements)
references
References 26 publications
54
683
3
7
Order By: Relevance
“…Our present finding of intermittent long-range synchrony at all passbands from theta to epsilon (aka high gamma) conflicts with the suggestion (Kopell et al, 2000;Von Stein and Sarnthein, 2000;Von Rullen and Koch, 2003) that long-range synchrony occurs only in low frequency bands (Arieli et al, 1995), while gamma oscillations are synchronous only in local networks or at most between a few cortical areas (Eckhorn, 1994;Steriade et al, 1996;Engel et al, 1991b;Roelfsema et al, 1997). In fact the suggestion that theta/alpha or theta/apha/beta synchrony is global while gamma or beta/gamma-synchrony is local has already been negated by numerous reports of long-range gamma synchrony coinciding with various conscious experiences (Haig et al, 2000;Bhattacharya et al, 2001;Gruber et al, 2001;Lutz et al, 2002;Summerfield and Mangels, 2005).…”
Section: Comparison Of Our Results With the Literaturecontrasting
confidence: 99%
“…Our present finding of intermittent long-range synchrony at all passbands from theta to epsilon (aka high gamma) conflicts with the suggestion (Kopell et al, 2000;Von Stein and Sarnthein, 2000;Von Rullen and Koch, 2003) that long-range synchrony occurs only in low frequency bands (Arieli et al, 1995), while gamma oscillations are synchronous only in local networks or at most between a few cortical areas (Eckhorn, 1994;Steriade et al, 1996;Engel et al, 1991b;Roelfsema et al, 1997). In fact the suggestion that theta/alpha or theta/apha/beta synchrony is global while gamma or beta/gamma-synchrony is local has already been negated by numerous reports of long-range gamma synchrony coinciding with various conscious experiences (Haig et al, 2000;Bhattacharya et al, 2001;Gruber et al, 2001;Lutz et al, 2002;Summerfield and Mangels, 2005).…”
Section: Comparison Of Our Results With the Literaturecontrasting
confidence: 99%
“…Physiological beta synchrony is promoted in expectation of impending perturbation to a desired posture [Androulidakis et al, 2007] but is also sensitive to the uncertainty of motor outcome estimation [Tan et al, 2016]. Beta oscillations may also contribute to long‐range communication across cortical regions [Engel and Fries, 2010; Kopell et al, 2000] and can facilitate modulation of selective attention in support of action selection [Grent‐'t‐Jong et al, 2013, 2014; Tzagarakis et al, 2010], beyond simple correlation with reaction times [van Ede et al, 2012]. The abnormalities in this characteristic motor system rhythm displayed by ALS patients (amplified beta desychronization and attenuated beta rebound) may reflect or even contribute to an excitotoxic degeneration of neural microcircuitry, particularly given the apparent correlation with rate of disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…Kopell et al (2000) proposed that γ and β oscillations might subserve different functional roles. Their simulations showed that β oscillations are more robust in synchronizing areas separated by larger transmission delays, whereas γ oscillations tend to be dispersed when significant delays are interposed.…”
Section: Discussionmentioning
confidence: 99%